Disciplinary Differences in Social Cataloging: A Comparison of LibraryThing Tagging of Works in Literature, History and Business. Issue 4 (2nd October 2021) - Hider, Philip; Steele, Gemma; Smeaton, Anya
ABSTRACT: Samples of works from the literature, history and business collections of a university library were searched in the LibraryThing (LT) social cataloging platform. Match rates were obtained, and the subject headings and LT tags of matching titles recorded. The tags were then compared across the three fields. Finally, the nature of those tags representing new concepts was analyzed. Findings suggest that literature and history are much more represented on LT than is business, but that even for this field LT covers over half the library's materials. While the amounts of tagging for literature, history and business were likewise very different, and the amounts that added retrieval value equally, or perhaps even more so, it was clear that access even to business titles could be greatly enhanced by social cataloging, when it was applied. This was reflected in the way that taggers focused on different types of concepts in the different fields, according to their audiences' different search needs